Предмет: Математика, автор: princessqaaaa

8,10
Очень СРОЧНО!!!!!!
ЗАРАНЕЕ ОГРОМНОЕ СПАСИБО

Приложения:

Ответы

Автор ответа: zhenyaM2002
0
8)  \frac{2a+3}{6-2a} =  \frac{2a+3}{-2(a-3)} = - \frac{2a+3}{2(a-3)} = - \frac{(2a+3)(a+3)}{2(a-3)(a+3)} = -  \frac{2a^2+6a+3a+9}{2(a^2-3^2)} = \\  \\ 
=- \frac{2a^2+9a+9}{2(a^2-9)}  \\  \\ 
10) \frac{11}{x+1} =  \frac{11*(x^2 - x*1+1^2)}{(x+1)(x^2-x*1 +1^2)} =  \frac{11(x^2-x+1)}{x^3+1^3} =  \frac{11x^2-11x+11}{x^3+1}
Похожие вопросы
Предмет: Алгебра, автор: ramirez1337